Scenario-based tsunami hazard assessment for the coast of Vietnam from the \(109^{o}\) Meridian fault zone - Nguyen Hong, Phuong; Bui Cong, Que; Vu Van, Phong; Pham The, Truyen (Vietnam Journal of Marine Science and Technology, 2022)
Located on the continental shelf and stretching approximately 1,000 km along the Central and Southern Central coasts of Vietnam, the 109o Meridian Fault system has long been recognized as seismically active. Empirical evidence of the seismic, volcanic, and submarine landslide activities also suggests that this fault might be capable of originating near-field tsunamis, which can harm the Vietnamese coastal zone. This paper investigates the possibility of the near-field tsunamis from the 109o Meridian Fault and their impact on the Vietnamese coasts. Location and segmentation of the 109o Meridian fault were determined using seismological, geophysical data, and geomorphologic evidence. The fault’s seismotectonic and geodynamic characteristics were used to model the tsunami source. The COMCOT model was used for simulating three worst-case tsunami scenarios excited by earthquakes with Mw = 8.0 originated in two different segments of the 109o Meridian Fault source. The relationship between tsunami wave height and the source-to-coast travel time is investigated in detail at the virtual sea-level stations distributed along the Vietnamese coastline. The simulation results are presented in the deep-ocean tsunami amplitude maps for the entire East Vietnam Sea region and the coastal tsunami amplitude maps for the Vietnamese coasts. The simulation results show the highest tsunami hazards concentrated along the Central and Southern Central Vietnam coastal zones (from Quang Nam province to Ba Ria-Vung Tau province), with the highest tsunami waves not exceeding 4 m observed off-shore the Quang Ngai, Phu Yen and Ninh Thuan provinces. The shortest tsunami travel time from the source to the Southern Central coast is 35 minutes. Due to its strike-slip mechanism, there is a low possibility of the 109o Meridian fault generating earthquake-triggered tsunamis. Moreover, even if they occurred, the near-field tsunamis generated from the 109o Meridian fault source can hardly cause severe damage and losses for the coastal zones of Vietnam, as shown by the simulation results. Nevertheless, the worst-case scenarios simulation results provide the highest risk that the near-field tsunamis from the 109o Meridian fault source might affect the Vietnamese coasts, which is helpful for the national tsunami warning and response purpose.